The use of Facebook in tertiary education: Case study of a unit-related Facebook page in a university justice class. Issue 4 (25th November 2013) - Renee Staines, Zoe; Lauchs, Mark
Abstract : Purpose: – This study aims to evaluate the usefulness of a university unit Facebook page, which was established to support a first-year university justice unit. The study pays particular regard to the Facebook page's impact on students learning outcomes and communications amongst students and between students and teaching staff. Design/methodology/approach: – All students enrolled in the unit were asked to complete an online survey, which sought to determine whether they used the unit Facebook page and if so, the nature and extent of their use. Findings: – The study found that the unit Facebook page was useful in achieving most learning objectives for the unit. This included enhancing students' knowledge and understanding of unit content, as well as their ability to critically analyse unit materials. Students also indicated that they found the Facebook page better than the university's central learning management system across a range of areas. It was particularly useful for facilitating unit-related discussions. Research limitations/implications: – The survey results reported in this paper are based on a relatively small sample of students ( n =67) from a first-year university justice unit. Future studies should seek to garner evidence from broader and larger samples that transcend specific unit populations. However, the findings of this study do indicate further support for the use of Facebook as a supplementary tool in university education. Originality/value: – This study focuses on two aspects of social networking technologies that have not been previously researched and thus contributes to the growing literature on the uses and benefits of Facebook in tertiary education.